2023
DOI: 10.1136/bmjopen-2022-070491
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ceftazidime–avibactam versus polymyxins in the treatment of carbapenem-resistant Enterobacteriaceae infection: a systematic review and meta-analysis

Abstract: ObjectivesCarbapenem-resistant Enterobacteriaceae is increasingly recognised as a significant public health concern. Ceftazidime-avibactam (CAZ-AVI) and polymyxins are considered as the last therapeutic options worldwide. This is the first meta-analysis of recently published data to compare the clinical efficacy and safety of CAZ-AVI with polymyxins in the treatment of carbapenem-resistant Enterobacteriaceae infections.DesignSystematic review and meta-analysis.Data sourcesPubMed, Embase and the Cochrane Librar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Lastly, Yang et al [55] performed a meta-analysis that aimed to compare the effectiveness and safety of CAZ-AVI versus polymyxins in the treatment of infections caused by CRE. The authors conducted a comprehensive literature search, and the studies they found involved a total of 1111 patients.…”
Section: Caz-avimentioning
confidence: 99%
“…Lastly, Yang et al [55] performed a meta-analysis that aimed to compare the effectiveness and safety of CAZ-AVI versus polymyxins in the treatment of infections caused by CRE. The authors conducted a comprehensive literature search, and the studies they found involved a total of 1111 patients.…”
Section: Caz-avimentioning
confidence: 99%